2017
DOI: 10.1038/bjc.2017.300
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the impact of a cancer diagnosis on life expectancy by socio-economic group for a range of cancer types in England

Abstract: Background:Differences in cancer survival exist across socio-economic groups for many cancer types. Standard metrics fail to show the overall impact for patients and the population.Methods:The available data consist of a population of ∼2.5 million patients and include all patients recorded as being diagnosed with melanoma, prostate, bladder, breast, colon, rectum, lung, ovarian and stomach cancers in England between 1998 and 2013. We estimated the average loss in expectation of life per patient in years and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 30 publications
3
40
0
Order By: Relevance
“…Similarly, patients in the least advantaged group experienced a significantly higher burden of cancer in terms of YLL (6.50% to 7.57%) compared with the richest (1.11%) from 2011 to 2015. Previous studies have also reported similar inequalities in YLL,75 76 whereas, a high proportion of patients in the most-deprived groups experienced very high years loss of life. Even though survival rates after cancer diagnosis have improved in recent years,7 disparities in cancer outcomes between the least-deprived and the most-deprived groups continue to persist.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Similarly, patients in the least advantaged group experienced a significantly higher burden of cancer in terms of YLL (6.50% to 7.57%) compared with the richest (1.11%) from 2011 to 2015. Previous studies have also reported similar inequalities in YLL,75 76 whereas, a high proportion of patients in the most-deprived groups experienced very high years loss of life. Even though survival rates after cancer diagnosis have improved in recent years,7 disparities in cancer outcomes between the least-deprived and the most-deprived groups continue to persist.…”
Section: Discussionsupporting
confidence: 65%
“…Similarly, the burden of cancer was high in New South Wales, Victoria and Queensland; however, the magnitude of fatal burden was unchanged during 2011 to 2015. Some previous studies have shown consistent findings, which have confirmed that the proportion of life lost for patients in geographical disadvantaged or low-resource settings had a higher cancer burden than their more advantaged counterparts 75 76. Socioeconomic inequalities in terms of poorer survival for geographically isolated patients was observed in cancer types in Australia including breast and colorectal cancer 86.…”
Section: Discussionmentioning
confidence: 55%
“…Andersson et al [7] have developed a model-based approach that involves extrapolating the excess and expected mortality curves in order to estimate the longterm all-cause survival. This approach has been shown to perform well empirically using historical data and has been applied in a number of settings [7,12,13,14,17]. Further steps can be taken to ensure the estimates are up-to-date by undertaking a period analysis approach [18,19].…”
Section: Methods and Examplesmentioning
confidence: 99%
“…We can calculate proportional, rather than the absolute loss in life expectancy, in order to report a metric that is more comparable across age, and is also a useful further metric for reporting [6,14]. Figure 4 shows the average proportion of life years lost for female cancer patients across the four cancer sites; the average number of years of life lost as a proportion of the average life years without cancer.…”
Section: Example 3 -Proportional Measures Of Life Expectancymentioning
confidence: 99%
See 1 more Smart Citation